Leadership Training Model Based On Outdoor Activity For Students - James Klemen Lika; James Tangkudung; Hernawan, Hernawan; Defliyanto, Defliyanto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2024)
This research aims to develop an instructional model based on outdoor activities to develop leadership skills at the college level. The research and development methodology followed the Borg and Gall model. The instructional model was designed by reviewing literature on leadership theories, outdoor education and experiential Training. Activities were selected based on targeted leadership skills, debriefing protocols, and sequences. The model was piloted in a field test involving 40 students. Leadership skills were measured before and after implementing the model. Quantitative results showed a significant improvement in all leadership practices for both small-group pilot testing and field testing. Qualitative feedback highlighted the development of communication behavior among team members, behavior of accepting suggestions and criticism, behavior of showing appreciation, behavior of showing respect, helping behavior, and patience behavior. Additionally, there are behaviors related to relevant knowledge, cooperation, motivation, self-confidence, discipline, and responsibility. This study validated that an intentionally designed outdoor activities-based instructional model can be an engaging and effective approach to developing leadership capacities in higher education. and responsibility. This study validated that an intentionally designed outdoor activities-based instructional model can be an engaging and effective approach to developing leadership capacities in higher education. and responsibility. This study validated that an intentionally designed outdoor activities-based instructional model can be an engaging and effective approach to developing leadership capacities in higher education.